2016
DOI: 10.1002/ece3.1872
|View full text |Cite
|
Sign up to set email alerts
|

The influence of simulated exploitation on Patella vulgata populations: protandric sex change is size‐dependent

Abstract: Grazing mollusks are used as a food resource worldwide, and limpets are harvested commercially for both local consumption and export in several countries. This study describes a field experiment to assess the effects of simulated human exploitation of limpets Patella vulgata on their population ecology in terms of protandry (age‐related sex change from male to female), growth, recruitment, migration, and density regulation. Limpet populations at two locations in southwest England were artificially exploited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
(199 reference statements)
2
16
0
Order By: Relevance
“…These results are also very similar to those found by Borges et al. () for P. vulgata in the British Isles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are also very similar to those found by Borges et al. () for P. vulgata in the British Isles.…”
Section: Discussionsupporting
confidence: 92%
“…As exploitation is mostly targeting the larger individuals (see Figure b), results suggest that males are compensating the removal mainly of the larger females, by undergoing sex change at smaller and presumably earlier sizes. That the size of the smallest male has remained relatively stable throughout the archipelago also suggests that the switch of neuters into males has not been affected (in contrast to Borges et al., in P. vulgata ). These results suggest that the numbers of males in the population must have been reduced in the most exploited islands.…”
Section: Discussionmentioning
confidence: 92%
“…Imbalances in the sex ratio of this species might be related to the possibility of P. aspera being a protandric hermaphrodite. Also, size selective harvest of this species might induce phenotypic pasticity in protandric hermaphrodite limpets as recently reported for Patella vulgata by Borges et al [56]. In heavily exploited populations of protandric hermaphrodite limpets, sex-change has been reported to occur at smaller sizes as a consequence of the size selective nature of limpet harvest, skewing sex-ratios and altering the reproductive output of those populations.…”
Section: Reproduction and Recruitmentmentioning
confidence: 51%
“…In such source populations, a density‐dependent effect could occur while carrying capacity is being achieved. In fact, Boaventura et al () and Borges, Hawkins, Crowe, and Doncaster () have demonstrated several effects of density on biological traits of limpets such as sex ratio, sex change, weight, and shell growth or survival. Nevertheless, the increasing density of the population in Parque del Mediterraneo is indicative of weak inter‐age class interactions, providing evidence that the carrying capacity has not yet been reached.…”
Section: Discussionmentioning
confidence: 99%